APLIKASI PEMESANAN TIKET ONLINE BERBASIS WEB: STUDI KASUS PANTAI SAYANG HEULANG - Rika; M. Syafiuddin Usman (Melati Institute, 2023)
South Garut is one of the areas that has a very wide stretch of beach and sea. Not only is it used as a source of livelihood for local fishermen, but its natural beauty invites a lot of migrants from various regions. One of the beaches in South Garut, Sayang Heulang Beach, has a problem, namely visitor services that are still carried out only with one offline ticket purchase portal on the spot. The purpose of making this online ticket booking application is to provide ticket purchase options online, not just offline. Making this application aims to make it easier for visitors to purchase tickets to be more effective and efficient. This application is made using the visual studio code application, while the programming language uses PHP, MySQL, as a database manager. The system development method used is waterfall. The result of this research is to produce a system that provides convenience for customers so that it helps the ticket ordering process more effectively and efficiently and does not cause queues.